Laser cutting for fashion and textiles - Baker, Laura Berens (Laurence King Publishing, 2016)
"Laser cutting is the latest embellishment technique to appear on the runway. In this book, Laura Berens Baker provides 14 inspirational projects that demonstrate how to use laser cutting equipment to produce original designs for garments and accessories. The book explores how to engineer designs and harness laser technology to upcycle fabrics, replicating traditional finishes as well as developing new ones"--Provided by publisher.